Ethiopia climate-smart agriculture roadmap - Eshete, Getachew; Assefa, Berhanu; Lemma, Esayas; Kibret, Girma; Ambaw, Gebermedihin; Samuel, Seble; Ahmed, Jemal Seid; Tesfaye, Kindie; Tamene, Lulseged D.; Haile, Aynalem; Asnake, Asaye; Mengiste, Amare; et al. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This roadmap is developed based on a context analysis of Ethiopian agriculture. The roadmap aims to strengthen the role of the Ministry of Agriculture (MoA) in addressing vulnerabilities facing the agriculture sector under changing climatic conditions by institutionalizing climate-smart agriculture. The roadmap is largely informed by the overarching country Climate Resilient Green Economy (CRGE) strategy; review of scientific literature; sectoral documents on Ethiopian agriculture and climate-smart agriculture; and related reports from government, development partners, scientific publications, expert comments on the draft and inputs obtained from several senior experts on two presentations made during climate-smart agriculture platform meetings conducted in May and November 2019.